EVALUATION OF THE EFFECTIVENESS AND USER EXPERIENCE OF THE SALI EDUCATION APPLICATION USING UEQ - Oky Irnawati; Kusmayanti Solecha; Yoseph Tajul Arifin; Sutan Arlie Johan (LPPM Nusa Mandiri, 2026)
CSA (Child Sexual Abuse) poses serious risks to preschool-aged children, yet culturally sensitive and developmentally appropriate learning tools remain scarce in Indonesia. This study evaluates the effectiveness and user experience of SALI, a gamified mobile application designed to foster early childhood body safety awareness. SALI integrates interactive storytelling, animated scenarios, and digital quizzes to help children recognize safe and unsafe touches in an engaging way. A pre–posttest design was applied with 46 children aged 4–6 years selected through purposive sampling. Children’s knowledge was measured using an in-app digital quiz, while parents assessed the app’s usability through the User Experience Questionnaire (UEQ), a standardized and validated instrument. Results showed that mean scores increased from 70.00 (SD = 31.55) in the pre-test to 94.98 (SD = 8.69) in the post-test. The Wilcoxon Signed Rank Test confirmed a significant improvement (Z = –5.382, p < 0.001), with an average N-Gain of 0.86 categorized as high. UEQ outcomes indicated positive ratings across all six dimensions, with attractiveness (M = 2.66) and efficiency (M = 2.61) scoring highest, while perspicuity (M = 2.18) scored lowest but remained within a positive range. These findings suggest that SALI not only improves children’s understanding of protective behaviors but also provides a satisfactory user experience for parents. The study contributes to both theory and practice by demonstrating how gamified mobile learning can serve as a foundation for developing adaptive and engaging CSA prevention curricula in early childhood education.